The Influence of Food and Beverages in Human Life According to Buya Hamka (Analysis Study of Tafsir Al-Azhar) - Fuady, Rifqy Jauhar; Akmaliyah, Akmaliyah (Indonesian Journal of Halal Research, 2020)
Al-Quran is a book of life, containing various rules concerning the order of human life in the world and the results of that life in the hereafter. Therefore it is certain that the Quran talks about food. The term food in Arabic is mentioned with 3 pieces of the terms. These are: "aklun, tha'am, and ghiza 'un. But of these three terms, the Quran uses only two, namely tha'am, and aklun. This study aimed to determine the influence of food in human life by taking a few verses in Quran according to Buya Hamka's point of view in Tafsir al-azhar. Based on the results of the discussion, Buya Hamka in interpreting food verses in Tafsir al-Azhar's cannot be separated from the correlation between verses one with the other verses, so that a complete understanding of the concept of food can be obtained. Based on the verses studied, it can be understood that the meaning of food in the interpretation of Buya Hamka, is grouped into various terms, namely, healthy food, eating food proportionally according to needs, having a sense of security towards food, food as a cry, food as a warning, and food as gift. The influence of food on human life has a profound effect on a person's soul, including praying, making the soul so calm, whereas a bribe is forbidden in one's stomach, then his worship will not be accepted for forty days, bad food will damage health and soul.